Arguments for the Existence of God in Ibn Sīnā’s Metaphysics: An Evaluation of the Problems of Divine Simplicity and Modal Collapse - Tugay Taşçı (Marifetname)

(untitled)
This article investigates the proof of God’s existence within Ibn Sīnā’s metaphysical framework, particularly addressing the concepts of divine simplicity and the problem of modal collapse. It commences by positioning Ibn Sīnā’s metaphysics in contrast to Aristotle’s, emphasizing the dynamic and evolutionary nature of Ibn Sīnā’s engagement with metaphysical inquiry. The article highlights Ibn Sīnā’s distinctiveness in redefining metaphysical exploration beyond physicalist presuppositions and establishing metaphysics as foundational for other scientific disciplines. Central to this exploration is the elucidation of Ibn Sīnā’s arguments for God’s existence, primarily through his concept of modality—encompassing the necessary, contingent, and impossible—and his unique argument known as The Proof of the Sincere (Burhān al-Siddiqīn). These arguments demonstrate Ibn Sīnā’s belief in the necessity of a being whose existence and essence are identical, countering Kantian critiques by emphasizing an ontological foundation rather than rational judgments alone. However, the assertion of the identity of existence and essence in the Necessary Being introduces the issue of divine simplicity and the potential for modal collapse—a challenge whereby distinctions between possible states of affairs are nullified. The article proposes that Ibn Sīnā’s distinction between general and special existence, alongside his theory of tashkīk al-wujūd (gradation of existence), offers avenues to navigate this philosophical challenge. Additionally, it suggests that Frege’s distinction between meaning and reference could further elucidate the discussion. The conclusion posits that while Ibn Sīnā’s arguments for God’s existence exhibit significant persuasive power, they also prompt further inquiries into divine simplicity and modal collapse. The exploration of these themes underscores the relevance of Ibn Sīnā’s metaphysical contributions to contemporary philosophical debates, advocating for a nuanced understanding of his work beyond traditional Aristotelian or Cartesian interpretations.